Transient processes of MoS2 tribofilm formation under boundary lubrication. (21st July 2016) - Rai, Y.; Neville, A.; Morina, A.
Abstract: A tribochemistry study that involves the application of Raman spectroscopy surface analysis has been undertaken to understand the time‐dependent tribochemical reactions, for lubrication by Molybdenum dialkyl‐dithiocarbamate (MoDTC) occurring in boundary lubricated conditions. Under the conditions of rubbing and high temperature, time‐resolved Raman spectroscopy results show the intermediate steps that lead to the MoDTC additive to be tribochemically structured on the wear scar of the contacting surface. A MoS2 tribofilm with a lattice layer structure is observed on the wear scar whenever the lowest friction was achieved. An apparent shift of the A1g and E2g Raman modes, indicating qualitative and quantitative information on the MoS2 tribofilm formed, is observed to be related to low friction. Detailed analyses of Raman spectra obtained on wear scars at different test durations and temperatures indicate that both temperature and rubbing are needed for the formation of low friction MoS2 tribofilm. Copyright © 2016 John Wiley & Sons, Ltd.